The Influence of Operational Expenses, Dividend Policy and Tax Expenses on Stock Returns - Goinones, Laoren Agustin (Syntax Corporation Indonesia, 2024)
This study intends to identify the influence of dividends policy operations expenses along with taxes burdens on stock returns. This research is a quantitative type of research carried out through analyzing the financial statements of companies in the Energy sectors listed on the Indonesian Stock Exchange (IDX) throughout the period from 2019 to 2022. The number of samples used in this study is 68 samples from 17 energy companies listed on the Indonesian Stock Exchange throughout the period from 2019 to 2022 through the use of the purposive sampling techniques. The data used in this study is secondary data in the form of financial statements from each company that has become a research samples. The variables selected in this study are Operating Expense (X1) as the first independent variables, Dividends Policy (X2) US the second independent variables, along with Taxes Expense (X3) US the third independent variables US well US Return on Shares (Y) US the bound variables. In this hypothesis test, multiple regression analysis and panel data assisted through the EViews 12 software programs were used. The results of this study shows that the best model is the Common Effect Model (CEM). The results of this study shows that Partials Operating Expenses (t-test) have an effect on Stock Returns, Dividends Policy partially (t-test) has no effect on Stock Returns and Tax Expenses partially (t-test) have no effect on Stock Returns. Meanwhile, simultaneously (test F) Operating Expenses, Dividends Policy and Taxes Expenses have an effect on Stock Returns. The contribution of the research to the variables of Operating Expenses, Dividends Policy and Taxes Expenses on Stock Return was 9.6%, while the remaining 90.4% was explained by other variables outside the research model.